2017
DOI: 10.1111/acps.12719
|View full text |Cite
|
Sign up to set email alerts
|

Perception of emotional prosody in adults with attention deficit hyperactivity disorder

Abstract: ADHD is associated with social cognition impairments involving both emotional prosody and empathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 18 publications
1
17
0
Order By: Relevance
“…Recent studies investigating adult patients with ADHD and their ability to perceive prosody and emotional faces showed that they displayed impaired performance, especially in the perception of angry emotional statements. These results were independent of executive skills (Bisch et al, 2016;Kis et al, 2017). Nevertheless, studies investigating social cognition in adults with ADHD (Uekermann et al, 2010), especially the association between social cognition and executive functions in adults with ADHD, are still rare.…”
Section: Introductionmentioning
confidence: 79%
See 4 more Smart Citations
“…Recent studies investigating adult patients with ADHD and their ability to perceive prosody and emotional faces showed that they displayed impaired performance, especially in the perception of angry emotional statements. These results were independent of executive skills (Bisch et al, 2016;Kis et al, 2017). Nevertheless, studies investigating social cognition in adults with ADHD (Uekermann et al, 2010), especially the association between social cognition and executive functions in adults with ADHD, are still rare.…”
Section: Introductionmentioning
confidence: 79%
“…Additionally, Kis et al (2017) were able to demonstrate an impaired perception of prosody as well as an impaired affective change of perspective. Additionally, Kis et al (2017) were able to demonstrate an impaired perception of prosody as well as an impaired affective change of perspective.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations